JACOBI FIELDS ON THE MANIFOLD OF FREUND - Arif, Muhammad Shoaib; Er-chuan, Zhang; Hua-fei, Sun (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, the geometric structures of Freund manifold are considered By defining a Riemannian metric, the curvature tensor and the scalar curvature are given. Then, the Jacobi fields on the Freund manifold have been considered to investigate the instability of the geodesics in view of diﬀerential geometry. Moreover, we take submanifold of Freund manifold as an example to illustrate our results.